2020
DOI: 10.1002/mus.27127
|View full text |Cite
|
Sign up to set email alerts
|

Proximal fibular nerve conduction studies to tibialis anterior: Optimal E2 (reference electrode) placement

Abstract: Background Several E2 (reference electrode) positions are described for fibular (peroneal) nerve conduction studies to tibialis anterior (TA). Methods This study compared the contribution of different E2 sites to the TA motor response, using remote referential recordings and different bipolar montages. Results The medial knee contributes minimal electrical activity to the bipolar TA recordings, whereas tibial, ankle, and toe references resulted in very similar, moderate amplitude contributions consistent with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(31 reference statements)
1
0
0
Order By: Relevance
“…14 B,C, third traces) ( Nandedkar and Barkhaus, 2020 ). Other authors have reported similar results ( Day, 2020 , Day, 2021 , Escorcio-Bezerra et al, 2019b ). The trade-off in minimizing E2 is that the CMAP amplitude and area will be lower than in the conventional montage, particularly in ulnar and tibial nerve studies ( Nandedkar and Barkhaus, 2007 ).…”
Section: Technical Considerations In Recording the Cmapsupporting
confidence: 70%
“…14 B,C, third traces) ( Nandedkar and Barkhaus, 2020 ). Other authors have reported similar results ( Day, 2020 , Day, 2021 , Escorcio-Bezerra et al, 2019b ). The trade-off in minimizing E2 is that the CMAP amplitude and area will be lower than in the conventional montage, particularly in ulnar and tibial nerve studies ( Nandedkar and Barkhaus, 2007 ).…”
Section: Technical Considerations In Recording the Cmapsupporting
confidence: 70%